Juridical Analysis of Law Number 11 of 2008 on Electronic Information and Transactions (ITE) and its Impact on Creative Economy Development in Indonesia - Judijanto, Loso; Khuan, Hendri (West Science Law and Human Rights, 2024)
This paper provides a juridical analysis of Law Number 11 of 2008 on Electronic Information and Transactions (ITE) and its impact on the development of the creative economy in Indonesia. The ITE Law was enacted to regulate online transactions and protect intellectual property, serving as a crucial framework for digital platforms that are essential to creative industries. However, the law has raised concerns regarding its vague defamation provisions, which have sometimes been applied in ways that stifle freedom of expression. Through a normative juridical approach and case study analysis, this research evaluates the effectiveness of the ITE Law in supporting the creative economy while identifying legal gaps and challenges in enforcement. The findings reveal that although the law provides necessary protections, reforms are needed to clarify its provisions and strengthen enforcement mechanisms to better serve Indonesia’s rapidly growing creative sector.